2021
DOI: 10.3390/separations8070103
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Group-Type Characterization of Plastic-Waste Pyrolysis Oils: By Comprehensive Two-Dimensional Gas Chromatography Including Linear, Branched, and Di-Olefins

Abstract: Plastic-waste pyrolysis oils contain large amounts of linear, branched, and di-olefinic compounds. This makes it not obvious to determine the detailed group-type composition in particular to the presence of substantial amounts of N-, S-, and O-containing heteroatomic compounds. The thorough evaluation of different column combinations for two-dimensional gas chromatography (GC × GC), i.e., non-polar × polar and polar × non-polar, revealed that the second combination had the best performance, as indicated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…Non-sulfur/nitrogen compounds are converted into non-chemiluminescent CO 2 and H 2 O in the oxidative combustion step ( Yan, 2002 ). GC × GC coupled to SCD and NCD have been applied for complex hydrocarbon samples in various publications and have proven to be valuable techniques for the analysis of trace amounts of sulfur ( Dijkmans et al, 2015 , Djokic et al, 2017 , Ruiz-Guerrero et al, 2006 , Hua et al, 2003 , Blomberg et al, 2004 ) and nitrogen ( Adam et al, 2009 , Adam et al, 2007 , Lissitsyna et al, 2013 , Ristic et al, 2016 , Dijkmans et al, 2015 , Wang et al, 2004 , Toraman et al, 2016 , Dao Thi et al, 2021 ), respectively (see Fig. 7 ).…”
Section: State-of-the-art Molecular Characterization Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…Non-sulfur/nitrogen compounds are converted into non-chemiluminescent CO 2 and H 2 O in the oxidative combustion step ( Yan, 2002 ). GC × GC coupled to SCD and NCD have been applied for complex hydrocarbon samples in various publications and have proven to be valuable techniques for the analysis of trace amounts of sulfur ( Dijkmans et al, 2015 , Djokic et al, 2017 , Ruiz-Guerrero et al, 2006 , Hua et al, 2003 , Blomberg et al, 2004 ) and nitrogen ( Adam et al, 2009 , Adam et al, 2007 , Lissitsyna et al, 2013 , Ristic et al, 2016 , Dijkmans et al, 2015 , Wang et al, 2004 , Toraman et al, 2016 , Dao Thi et al, 2021 ), respectively (see Fig. 7 ).…”
Section: State-of-the-art Molecular Characterization Techniquesmentioning
confidence: 99%
“…In order to improve the separation of heteroatomic compounds such as sulfur and nitrogen containing compounds as well as oxygenates from the dominant complex hydrocarbon matrix it is possible to use reversed-phase GC × GC using the polar column first, followed by the non-polar column. This specific mechanism was used by ( Dao Thi et al, 2021 ) and ( Toraman et al, 2014 ) who reported improved accuracy for the characterization of plastic waste pyrolysis oils.
Fig.
…”
Section: State-of-the-art Molecular Characterization Techniquesmentioning
confidence: 99%
See 3 more Smart Citations